Financial analysis of large‐volume delayed sampling to reduce bacterial contamination of platelets. Issue 5 (10th April 2020) - Kacker, Seema; Katz, Louis M.; Ness, Paul M.; Bloch, Evan M.; Goel, Ruchika; Gehrie, Eric A.; Lokhandwala, Parvez M.; Tobian, Aaron A.R.
Abstract : BACKGROUND: Effective and financially viable mitigation approaches are needed to reduce bacterial contamination of platelets in the US. Expected costs of large‐volume delayed sampling (LVDS), which would be performed by a blood center prior to shipment to a hospital, were compared to those of pathogen reduction (PR), point‐of‐release testing (PORt), and secondary bacterial culture (SBC). METHODS: Using a Markov‐based decision‐tree model, the financial and clinical impact of implementing all variants of LVDS, PR, PORt, and SBC described in FDA guidance were evaluated from a hospital perspective. Hospitals were assumed to acquire leukoreduced apheresis platelets, with LVDS adding $30 per unit. Monte Carlo simulations were run to estimate the direct medical costs for platelet acquisition, testing, transfusion, and possible complications associated with each approach. Input parameters, including test sensitivity and specificity, were drawn from existing literature and costs (2018US$) were based on a hospital perspective. A one‐way sensitivity analysis varied the assumed additional cost of LVDS. RESULTS: Under an approach of LVDS (7‐day), the total cost per transfused unit is $735.78, which falls between estimates for SBC (7‐day) and PORt. Assuming 20, 000 transfusions each year, LVDS would cost $14.72 million annually. Per‐unit LVDS costs would need to be less than $22.32 to be cheaper per transfusion than all other strategies, less than $32.02 to be cheaper than SBC (7‐day), and less than $196.19 to be cheaper than PR (5‐day). CONCLUSIONS: LVDS is an effective and cost‐competitive approach, assuming additional costs to blood centers and associated charges to hospitals are modest.